Case Report: Co-existence of a novel EXOC4‐TRHDE gene fusion with PML-RARA in acute promyelocytic leukemia - Liu, Xiaodong; Li, Wanting; Xiao, Jian; Zhong, Huixiu; Yang, Kun (Frontiers in Oncology, 2023)
Acute promyelocytic leukemia (APL) is characterized by t(15;17)(q22;q21), involving the promyelocytic leukemia protein (PML) gene on chromosome 15 and the retinoic acid receptor (RARA) gene on chromosome 17, leading to the creation of the PML-RARA chimeric gene. However, additional chromosomal abnormalities occur in approximately one third of patients with newly diagnosed APL. Here, we report a case of APL with co-existence of a novel translocation t(7;12)(q32;q13) involving an out-of-frame fusion between EXOC4 and TRHDE, together with PML-RARA. The patient achieved complete remission after treatment with conventional therapy with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). Although the causative link between EXOC4‐TRHDE and PML-RARA has yet to be established, the patient had a good response to therapy, suggesting that the EXOC4‐TRHDE fusion does not affect the efficacy of combined treatment with ATRA and ATO.